THE INFLUENCE OF READING TO LEARN (R2L) MODEL ON STUDENTS' COGNITIVE ABILITY ABOUT HUMAN DIGESTIVE SYSTEM - Aulia, Putri; Oktavia, Rani (Universe, 2024)
The implementation of the learning process in the 2013 curriculum uses a scientific approach. Ideally, learning using a scientific approach should be accompanied by a high interest in reading. The purpose of this study was to identify the effect of the Reading to Learn (R2L) model on students' cognitive abilities in the topic of the human digestive system. The type of study used in this research is quantitative research with the research method being quasi-experimental design (Quasi Experimental Design). Pretest-Posttest Nonequivalent Control Group Design was used in this research. The population in this study were all grade VIII students of SMPN 29 Padang who were enrolled in the 2022/2023 academic year. The sample was carried out by purposive sampling technique. Data on student cognitive ability in this study are pretest scores, posttest scores and gain scores. Based on data analysis with the t test, the results show that tcount> ttable, so that there is a significant influence on the application of the Reading to Learn learning model on students' cognitive abilitiy.